Sonographic Findings in Inflammatory Arthritis Secondary to Immune Checkpoint Inhibition: A Case Series. Issue 5 (12th June 2019) - Albayda, Jemima; Dein, Eric; Shah, Ami A.; Bingham, Clifton O.; Cappelli, Laura
Abstract : Objective: Immune checkpoint inhibitors (ICI) are transforming the field of oncology, leading to tumor regression in multiple advanced cancers. With this case series, we review the ultrasound imaging findings in a series of patients with ICI‐induced inflammatory arthritis (IA), a novel rheumatic disease that is caused by cancer immunotherapy. Methods: We identified patients with rheumatologist‐diagnosed, ICI‐induced IA who had musculoskeletal ultrasound performed for clinical care. A retrospective chart review was done to obtain demographics, oncologic history, clinical presentation, imaging, and synovial fluid results. Ultrasound images were reviewed and scored for synovial and tendon pathology, presence of Doppler, and bony erosion. Results: Nine patients were included in this study with a total of 18 joint regions assessed. The knees were the most commonly imaged joint followed by the hands, wrists, feet, and ankles. Synovitis was seen in 12 of the 18 joints with active Doppler in 50% of the cases. Tendon involvement was also frequently seen (13 of 18 joints) with tenosynovitis, tendinitis, and enthesophytes. Erosions were less frequent and seen in only three cases but were also an early finding. Conclusion: Patients with ICI‐induced IA had a wide range of pathology affecting the synovium, tendons, and bones on musculoskeletal ultrasound. Further systematic study with imaging is needed for this group of diseases.